Aplikasi Breast Care Terhadap Ketidaknyamanan Pasca Partum Ibu Dengan Bendungan ASI - R. Afrina; Nuriasni Nuriasni; Nurul Ainul Shifa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Postpartum discomfort is a nursing problem that is often experienced by mothers in the postpartum period. One of them is caused by breast enggorgement. The symptoms experienced are pain and the mother's breasts harden making it difficult to breastfeed. Breast care intervention for problems of postpartum discomfort ‘caused by breast enggorgement. A case study that aims to describe the application of breast care to clients with nursing problems of postpartum discomfort with breast enggorgement. The number of respondents in this case study research amounted to 2 mothers post second day sectio caesaria surgery. Breast swelling assessment using the Six Point Self-rated Engorgement Scale (SPES) with a score of 1-6. In addition, breast care interventions used standard operating procedures and action observation forms. The results of the case study showed that both patients who performed breast care experienced a decrease in the ix Point Self-rated Engorgement Scale (SPES) score from 4 to 3, with breast criteria still enggogerment but pain level was reduced. Breast milk (ASI) becomes smooth and breastfeeding the baby becomes easier. The implementation of breast care can reduce pain and swelling in the breast.for mother wirh discomfort after birth.